Penggunaan Media Lingkungan Dalam Pembelajaran IPA di Kelas IV SDN 11 Sengkuang Bora - Ana, Lusi; Khoiri, Ahmad; Suyatmin, Suyatmin (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2025)
Abstract: This research is based on the use of Environmental media in science learning. The purpose of the study was to determine the use of Environmental media in science learning in the fourth grade of SDN 11 Sekuang Bora. Research methods using qualitative descriptive qualitative approach. Research subject class teacher and fourth grade students SDN 11 Sekuang Bora. Object of research the use of Environmental media in science learning. Data collection techniques using interviews and documentation. Data analysis includes data reduction, data exposure and conclusion. Checking the validity of data using triangulation techniques. The results obtained that the learning steps using Environmental media that is to explain what material is learned, observation or observe directly what is learned. The learning steps carried out by teachers and students are based on Lesson Plan guidelines used by teachers in using Environmental media. Teachers use Environmental media in science learning such as plants, animals, and rocks around the school in explaining the material to students. The use of Environmental media in science learning is known that fourth grade teachers apply directly in the process of learning science in everyday life by studying the objects studied. Teachers use direct learning methods in introducing the environment to students by observing objects directly. The use of Environmental media in the science learning process has a good impact on students ' interest and knowledge in learning. Keywords: Environmental Media, Learning, Science Abstrak: Penelitian ini didasari oleh penggunaan media lingkungan dalam pembelajaran IPA. Tujuan penelitian mengetahui penggunaan media lingkungan dalam pembelajaran IPA di kelas IV SDN 11 Sekuang Bora. Metode penelitian menggunakan kualitatif dengan pendekatan deskriftif kualitatif. Subjek penelitian guru kelas dan siswa kelas IV SDN 11 Sekuang Bora. Objek penelitian penggunaan media lingkungan dalam pembelajaran IPA. Teknik pengumpulan data menggunakan wawancara dan dokumentasi. Analisis data meliputi reduksi data, paparan data dan penarikan kesimpulan. Pengecekan keabsahan data menggunakan triangulasi teknik. Hasil penelitian diperoleh bahwa langkah-langkah pembelajaran menggunakan media lingkungan yaitu menjelaskan materi apa yang dipelajari, observasi atau mengamati secara langsung apa yang dipelajari. Langkah-langkah pembelajaran yang dilakukan guru dan siswa berdasarkan pedoman RPP yang digunakan guru dalam menggunakan media lingkungan. Guru menggunakan media lingkungan dalam pembelajaran IPA seperti tumbuhan, hewan, dan batu-batuan yang ada di sekitar sekolah dalam menjelaskan materi kepada siswa. Penggunaan media lingkungan dalam pembelajaran IPA diketahui bahwa guru kelas IV mengaplikasikan secara langsung dalam proses pembelajaran IPA dalam kehidupan sehari-hari dengan mempelajari objek yang dipelajari. Guru menggunakan metode pembelajaran langsung dalam mengenalkan lingkungan kepada siswa dengan mengamati objek secara langsung. Penggunaan media lingkungan dalam proses pembelajaran IPA memberikan dampak yang baik terhadap minat dan pengetahuan siswa dalam belajar. Kata Kunci: Media, Lingkungan, Pembelajaran IPA